The Impact of Gadget Use During Pregnancy: A Systematic Literature Review (SLR) - Yanti, Eka Safitri; Damayani, Ayi Diah (Women, Midwives and Midwifery, 2025)
Background: The widespread use of mobile phones and electronic media devices (EMDs) has raised public health concerns, particularly regarding their potential effects during pregnancy. Pregnant women may be at increased risk of adverse maternal and fetal outcomes due to exposure to electromagnetic fields (EMFs) and prolonged screen time. Despite the growing body of research, comprehensive syntheses specifically addressing gadget use during pregnancy remain limited. Purpose: This systematic review synthesizes evidence on the effects of gadget use during pregnancy on maternal health and fetal development. Methods: This study employed a systematic literature review approach guided by the PRISMA framework. Relevant literature was retrieved from the Scopus and Google Scholar databases using specific keywords related to gadget use and pregnancy. The inclusion criteria comprised peer-reviewed articles published between 2015 and 2025, written in either English or Indonesian, that involved pregnant women and examined physical, mental, or developmental outcomes. The quality of the 19 selected studies was evaluated using the Mixed Methods Appraisal Tool (MMAT), and data extraction covered study design, outcomes, and key implications. Results: Nineteen studies met the inclusion and quality criteria, comprising mostly quantitative non-randomized designs. The findings show that excessive gadget use during pregnancy—particularly prolonged screen exposure and mobile phone use—is associated with increased maternal anxiety, depression, hypertensive disorders, lower birth weight, shortened gestational periods, and developmental issues in children, including speech delays and poor motor skills. However, a few studies reported no significant cognitive impact on offspring. Conclusion: Prolonged electronic device use during pregnancy has been associated with adverse maternal and fetal health outcomes. Given the potential risks, healthcare providers should recommend limiting screen exposure and developing clearer guidelines for safe gadget use during pregnancy. Further research is needed to define exposure thresholds and explore long-term impacts on child health.